Manual therapy associated with topical heat reduces pain and self-medication in patients with tension-type headache - Maisa Soares Gui-Demase; Kelly Cristina da Silva; Gisely dos Santos Teixeira (Universidade de São Paulo, 2021)
ABSTRACT Tension-type headache (TTH) is a significant public health problem. The myofascial trigger points in the masticatory and cervical muscles are related to pain located in the temporomandibular joint, face, and cranium according to specific patterns. Thus, therapeutic procedures should be directed to myofascial trigger points rather than to the area of referred pain. For this purpose, the massage therapy combined with the topical heat can provide effective results due to the increase of the local microcirculation, improving tissue perfusion and promoting muscle relaxation. In this study we investigated the effects of manual therapy associated with topical heat therapy in TTH pain. This is a single-arm study composed of 13 participants with TTH (females), which were submitted to a three-month research protocol. In the first month , they filled out a pain diary and then they were evaluated. In the following month, the treatment protocol was applied (8 sessions of 45 minutes, twice a week, involving massage for skin desensitization, myofascial trigger point deactivation and stretching (friction massage) on masticatory and trapezius muscles after the topical heat). Then, in the third month (follow-up period), the participants were instructed to fill out the pain diary once again. We observed a significant decrease in pain intensity in TTH episodes, and medication intake after treatment and it keeps decreasing in follow-up. We conclude that the combination of manual therapy protocol and topical heat reduced pain and episodes related to TTH, and self-medication use in our sample.